Description of Particle Size, Distribution, and Behavior of Talc Preparations Commercially Available Within the United States. Issue 1 (January 2018) - Gilbert, Christopher R.; Furman, Benjamin R.; Feller-Kopman, David J.; Haouzi, Philippe
Abstract : Background: Widespread use of talc pleurodesis remains controversial for many providers concerned by adverse events such as respiratory failure, which are sometimes fatal. Particle talc size has been implicated in these adverse effects, mainly on the basis of animal studies utilizing large amounts of talc or in observational studies performed on different continents with different talc preparations and doses. Our aim was to determine the particle size and distribution of only the commercially available US-talc preparations and whether the fluid content can affect this distribution. Methods: Commercially available US talc was evaluated under scanning electron microscopy and dynamic light scattering (DLS). Distribution of talc particle size was obtained in saline and various protein-based solutions. Results: Talc particle size by DLS was performed with commercially available Sterile Talc Powder and Sclerosol Intrapleural Aerosol. Sterile Talc Powder demonstrated a median diameter of 26.57 μm with a range of particle sizes from 0.399 μm to 100.237 μm. Sclerosol demonstrated a median diameter of 24.49 μm with a range of particle sizes from 0.224 μm to 100.237 μm. The exposure of talc to a protein rich environment (bovine serum albumin and human pleural fluid) led to the development of measureable, new, larger aggregated particle (>100 μm). Conclusions: Currently available US talc seems to have size characteristics similar to previous described "graded" talc preparations. The exposure of talc to a protein rich environment seems to modify the overall distribution of talc particle size when examined by DLS.